Inheritance Property Distribution Models Among the Muslim Community of Borneo-Nusantara - Hasan, Muhammad; Ma'u, Dahlia Haliah; Sahid, Muallimin Mochammad (al-'adalah, 2024)
This article is aimed at describing the model of transfer of property to heirs in the inheritance of the Muslim community of Borneo-Nusantara. On the one hand, the Muslim community of Borneo is obedient and subject to the doctrine of Islam, but on the other hand, they also cannot avoid the local culture that lives in the Borneo community. This research is classified as descriptive-qualitative research using a legal sociology approach. Data collection was carried out through electronic and manual searches from sources in the form of books, manuscript articles, or other information materials related to the problem being studied. Data analysis was carried out using content analysis techniques. This study found that there were at least 6 models of transfer of property to heirs practiced by the Muslim Community of Borneo-Nusantara, namely: 1) farāidh-ishlāh, 2) ishlāh (deliberation), 3) hibah-wasiat, 4) hibah, 5) wasiat, and 6) munāsakhahwhich are carried out by each ethnic group in every place in Borneo-Nusantara according to the needs and socio-cultural of the surrounding community. This study concludes that the inheritance system among the Muslim community of Borneo Nusantara is implemented dynamically following the socio-cultural development of the local community. This phenomenon is a unique characteristic of the transfer of property in the inheritance system of the Muslim community of Borneo-Nusantara that contributes practically to solving inheritance problems.